Two new species of ground crickets (Orthoptera: Trigonidiidae; Nemobiinae) from China - He, Zhixin; Wang, Ning; Huang, Huateng; Ma, Libin (Zootaxa, 2022)
Here we describe two new species of ground crickets from Yunnan Province, China (Homonemobius brevipennis sp. nov. and Pteronemobius osuviridis sp. nov.). Descriptions, illustrations, and distributions of these new species are provided.